Metacercárias de Diplostomum (Austrodiplostomum) compactum Lutz, 1928 (Digenea, Diplostomidae) em peixes do rio Paraná, Brasil. Prevalência, sazonalidade e intensidade de infecção - Santos, Rosemeire de Souza; Pimenta, Franco Dani Akira; Martins, Maurício Laterça; Takahashi, Haroldo Kazuyuki; Marengoni, Nilton Garcia (My University, 2002)
This paper aims at evaluating the occurrence of Diplostommn (Anstrodiplostomum compactum (Digenea: Diplostomatidae) in the eyeball of Plagioscion sqnamosissimus (corvina) and Cichla ocellaris (tucunaré), monthly captured in Paraná river, Presidente Epitácio, state of São Paulo, Brazil. From 61 corvinas under analysis, 56 of them contained parasites (92%) with intensity rate of 42.0 host parasites. From an amount of 81 tucunarés, 45 contained parasites (55%) with intensity rate of 9.3 parasites. Corvinas showed prevalence from 71 to 100% with the highest intensity rates (103.3 and 106.9) from February to March, 2001. Comparatively, the tucunaré showed the highest prevalence from November 2000 (90%) to February 2001 (80%). The tucunaré highest intensity rates occurred on September, 2000 (12.7), December, 2000 (12.2) and February, 2001 (16.1). Metacercariae showed a hollow womb body and a posterior region of a sinuous conic protuberance, an oral sucker smaller than the acetabulae, a simple acetabulae located in the pre-equatorial region of helminto. A short pre-pharynx followed by a muscular pharynx, genital pore next to acetubulae. Corvina metacercariae presents 1.434,0 μm (880 to 1.840) long by 611.2 ± 93.4 μm (400 to 792) wide. Tucunaré metacercariae, 1.462.4 μm (960 to 2.480) by 710.8 μm (560 to 960). Authors confirmed corvina great susceptibility to Diplomastum and the relationship between the parasitism and the aquatic and climatic parameters.
Metacercariae of Diplostomum (Austrodiplostomum) compactum Lutz, 1928 (Digenea, Diplostomatidae) in fishes of Paraná River, Brazil. Prevalence, seasoning and intensity of infection
Keywords: Cuchla ocellaris; Description; Diplostomum; Plagioscion squamosissimus; Prevalence; Seasoning; animal parasitosis; Brazil; cichla ocellaris; diplostomum compactum; eye; fish; genital system; helminth; infection rate; morphometrics; nonhuman; parameter; parasite prevalence; parasitism; pharynx; plagioscion squamosissimus; river; seasonal variation; Animalia; Cichla; Cichla ocellaris; Diplostomatidae; Diplostomum compactum; Pisces; Plagioscion; Vermes